Switching Behavior pada Konsumen Klinik Kecantikan di Kota Surabaya - Yulfajar, Amrina; Rofiaty (Jurnal Aplikasi Manajemen, 2014)
This study used qualitative method with phenomonlogy apparoach, to have a deep insight of switching behavior of beauty cliniq consumer. The phonemena is describe as the pattern of first swithing behavior of first decision of beauty cliniq and then switch into another beauty cliniq. The informant of this study are collected by using snowball sampling method. Collecting data in this study through in-depth interview process to each informant. Data analysis was done by coding. In the next phase, the researcher makes the descriptive data from interviews with informants to obtain the switching berhavior patterns of beauty clinic consumer according to the categories that have been found.Based on the data analysis, it is found there are two themes why consumers choose the beauty clinic for the first time, there are Reference Group Influence and Availability of Doctor. When Switching to another beauty clinic, found four themes, there are, Reference Group Influence, Convenience, Service, and Core Services Failure. At the end of the study, there were no relationships between demographic data informants with the results of the study.